Двухспектральный фотоприемник - Dobrovol’sky, Yu. G.; Komarov, E. V.; Biksej, M. P. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The results of research and development of a dual-spectral photodetector, in which photodiodes are arranged one above the other, are presented. The photodetector is characterized by the increased sensitivity of the upper photodiode. It is shown that the optimal design is one in which the contact on the back side of the crystal is formed as a lattice structure, in which areas occupied by metallization alternate with areas free of it. The dimensions of the cells are determined by the dimensions of the optical probe.